Case Report: Organ procurement in a DCD donor with ovarian thecoma: abdominal NRP enabled timely and safe resection, pathological confirmation, and successful kidney transplantation - Assouline, Benjamin; Olivier, Timothée; Rougemont, Anne-Laure; Compagnon, Philippe; Wassmer, Charles-Henri; Quintard, Hervé; Bendjelid, Karim; Immer, Franz; Giraud, Raphaël (Frontiers in Transplantation, 2025)
BackgroundDonation after circulatory death (DCD) may be complicated by incidental findings, including tumor lesions that require urgent diagnosis. Here, we describe the case of a DCD donor with a large adnexal mass. Abdominal normothermic regional perfusion (A-NRP) enabled the safe resection of the mass, real-time pathological analysis, and subsequent kidney transplantation.Case summaryA 60-year-old woman suffered a hypoxic cardiac arrest and subsequently remained in a deep coma with poor neurological prognostic indicators. In accordance with her presumed wishes, life support was withdrawn, and a controlled DCD procedure with A-NRP was initiated. Imaging revealed a 27-cm adnexal mass. Laboratory markers showed elevated cancer antigen 125 (CA 125) but low cancer antigen 19-9 (CA 19-9) and carcinoembryonic antigen (CEA), and cytology was negative. Bilateral oophorectomy was performed under A-NRP, and the frozen section excluded malignancy, with final pathology confirming an ovarian thecoma. Both kidneys were procured; only the left kidney was transplanted successfully. The recipient experienced immediate diuresis and regained stable renal function at 1 month.DiscussionThis case illustrates how A-NRP provides oxygenated perfusion while allowing time for surgical excision and a pathological diagnosis of incidental tumors. It prevented unnecessary donor exclusion and enabled transplantation.ConclusionIn selected DCD donors with incidental lesions, A-NRP can safely bridge the diagnostic process, preserve organ viability, and expand the donor pool.